Estimation and Analysis of Water Environment Capacity: A Case Study of Huaxi Watershed in Guizhou Province. Issue 1 (June 2020) - Dong, Haiyang; Chong, Lin; Guo, Cong
Abstract: A one-dimensional water quality mathematical model was put forward to calculate the water environmental carrying capacity(WECC) for rivers in Huaxi District. The river system of Huaxi district is divided into four basins. Based on field observation and numerical simulation, the pollutant degradation coefficients and diffusion coefficient for different river districts were determined to explore the WECCs of COD, NH3 -N and TP. It reflects the pollutant carrying capacity of different basins under the hydrological condition of 90% guarantee rate, which plays an important role in pollution control and water environmental protection.